The Role of Digital Technologies in Maintaining the Mental Health of Foreign Language Teachers - Zinukova, Nataliia; Korobeinikova, Tetiana (Educological discourse, 2024)
The article examines the complex and multifaceted role of digital technologies in maintaining and preserving the mental health of foreign language teachers. In the context of the constantly growing use of digital tools in the educational process, the study opens a discussion about how digitalization affects the efficiency, organization and quality of work of foreign language teachers. On the one hand, digital tools open up new horizons for pedagogical practice, giving teachers access to a variety of educational resources, innovative teaching methods, and tools for effective time and materials management. This, in turn, can contribute to an increase in overall efficiency and job satisfaction, as well as provide new opportunities for professional development. However, along with the benefits of digital technologies, the article also draws attention to their potential risks and negative consequences. In particular, it focuses on issues such as digital burnout caused by excessive use of technology, feelings of isolation due to the reduction of direct interpersonal contacts and the risk of information overload. The article examines how these factors can negatively affect the psychological well-being of foreign language teachers, causing stress and a decrease in professional motivation. The authors emphasize the importance of providing effective psychological support, which can be a key element in preventing and solving these problems. The paper also highlights the need for further research in this area, emphasizing the importance of developing new strategies and approaches that can contribute to a better understanding and resolution of digital challenges. In particular, the authors call for research into the effectiveness of various methods of psychological support, the study of the impact of digital technologies on various aspects of mental health, and the development of holistic programs that include digital literacy training, stress management strategies, and techniques for supporting social interaction. In general, the aim of these studies is not only to improve the quality of the professional life of foreign language teachers, but also to ensure their general well-being in a rapidly changing digital world. The authors emphasize that such research is important not only for maintaining the individual health of teachers, but also for ensuring the sustainable development of educational institutions as a whole.